The Influence of The Android-Based Numtrack Kids Application on Numeration Literacy in Children Aged 4-6 Years in Ra Akbar Kemayoran, Central Jakarta - Setiowati, Ike; Puridawaty, Brigita (Journal of Scientific Research, Education, and Technology (JSRET), 2025)
This research aims to determine the effect of using the Android-based NumTrack Kids application on numeracy literacy skills in children aged 4-6 years at RA Akbar Kemayoran, Central Jakarta. This research method is quantitative with an experimental approach (pre-experimental design) which includes treatment. The data obtained from this research are the results of abilities before and after carrying out the Android-based learning process using the "Numtrack kids" application. The pretest carried out in this research was carried out without using the "Numtrackids" application. Meanwhile, the final posttest results were obtained from children's numeracy literacy skills using the "Numtrack kids" application. The research population was 43 with a research sample of 21 children. The t test results obtained a sig value = 0.002, which is smaller than α = 0.05. Thus, this means that there is an influence of the Android-based Numtrack Kids application on the Numeracy Literacy abilities of children aged 4-6 years at RA Akbar Kemayoran, Central Jakarta.